Green flexible polyurethane foam as Fe-Si adsorbent support for the removal of methylene blue from aqueous solution - Ahmad, Afiqah; Md. Jamil, Siti Nurul Ain; Choong, Thomas Shean Yaw; Abdullah, Abdul Halim; Mastuli, Mohd Sufri; Othman, Nurhanisah; Jiman, Nurnazurah (MDPI AG, 2019)
This paper describes the preparation, characterisation, and potential application of flexible palm oil-based polyurethane foam (PUF) as a support for iron-silica (Fe-Si) adsorbent. Fe-Si/polyurethane composite (Fe-Si/PUC) was prepared by impregnating Fe-Si adsorbent onto the surface of PUF by using a novel immersion-drying method. Morphological analysis of Fe-Si/PUC proved that Fe-Si was successfully impregnated onto the surface of PUF. Compression test and thermogravimetric analysis were carried out to determine the flexibility and thermal stability of Fe-Si/PUC, respectively. The Fe-Si/PUC removed 90.0% of 10 ppm methylene blue (MB) from aqueous solution in 60 min. The reusability study showed that Fe-Si/PUC removed 55.9% of MB on the seventh cycle. Hence, the synthesis of Fe-Si/PUC opens up a new path of implementing palm oil-based PUF to assist in the recovery of an adsorbent for environmental clean-up. The mechanism of physical interaction during the impregnation of Fe-Si adsorbent onto PUF was proposed in this paper.